Altitude training recommendations in preparation for competition at altitude - 2011 Pan American Games Guadalajara, Mexico - Chapman, R.; Wilber, R.; Shannon, M. (2011)
The 2011 Pan American Games will be held in Guadalajara, Mexico from October 23 - 30. Guadalajara is located at an altitude of 5150ft, which will have a significant slowing impact on distance races of 1500m and longer. However, with proper preparation and acclimatization to altitude in advance of the meet, distance athletes can reduce the effects of altitude and maximize race performance.